2019
DOI: 10.3390/su11102974
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Choice Behavior of Taxis and Express Services Based on the SEM-Logit Model

Abstract: With the development of Internet technology, online car-hailing is booming in China, which has profoundly affected people’s travel structures. In order to seek the sustainable development of taxi and online car-hailing services from the perspective of passenger mode choice behavior, the mechanism of passengers’ decision-making procedures and their travel mode choice behaviors were analyzed. To study the influence of latent variable factors on passenger choice behavior, this paper firstly designed a questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…For instance, bike-sharing users are more inclined to switch to ridesourcing service on rainy days because of bad cycling conditions. These findings support previous studies of Sun and Si where it is found that the rainy days could bring the great increase of ridesourcing trips, which may involve partial original trips of bike-sharing (72,43). As the riding distance increases, bike-sharing users are more likely to choose ridesourcing for long-distance trips, which is consistent with the above findings about the impact of trip distance on travel mode choice.…”
Section: Model Performance On Shared Mobility Usagesupporting
confidence: 92%
“…For instance, bike-sharing users are more inclined to switch to ridesourcing service on rainy days because of bad cycling conditions. These findings support previous studies of Sun and Si where it is found that the rainy days could bring the great increase of ridesourcing trips, which may involve partial original trips of bike-sharing (72,43). As the riding distance increases, bike-sharing users are more likely to choose ridesourcing for long-distance trips, which is consistent with the above findings about the impact of trip distance on travel mode choice.…”
Section: Model Performance On Shared Mobility Usagesupporting
confidence: 92%
“…However, from the view of psychology, the "indifference threshold" can be understood as a traveler's sensitivity to changes in travel utility. Many scholars have studied the influence of psychological factors on travel behavior [16][17][18][19]. For example, Christian et al [20] established a structural equation model based on the theory of planned behavior, and discussed the influence of psychological factors such as "behavioral intention", "subjective norms", "behavioral habits", and "external environment" on environmentally friendly travel behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…When there is a shortage of bus metros, the ridership density of net cars and taxis is higher [38][39][40]. It may be that public transport systems do not have an advantage in terms of long-distance commuting, with numerous studies showing that residents prefer to take taxis over buses for longdistance commuting [41] and that high-income residents of new city areas prefer other types of travel such as car and taxi transport [6,42], as this not only eliminates the need for intermediate transfers but also makes travel more comfortable overall. When we compare Figure 5, the aggregated relationship between rail transit distribution and the commuting pollutions of carbon by residential taxi transports, we also find that residential commuting carbon emissions by taxi travel are lower in areas with a higher density of public transport facilities.…”
Section: The Impact Of Urban Spatial Structure and The Construction O...mentioning
confidence: 99%